Análisis de la ley orgánica para la reactivación de la economía del ecuador y su incidencia en la empresa exportadora “rosas del Cotopaxi cía. Ltda.” ubicada en la parroquia de Mulaló, cantón Latacunga, provincia de Cotopaxi, en el período económico 2017. - Camalle Chiliquinga, Delia Margoth (2018)
This research entitled "Analysis of the Organic Law for the economy reactivation of Ecuador and its impact on the export company" Rosas del Cotopaxi "CIA. LTDA, located in the Mulaló parish, Latacunga canton, Cotopaxi province, on economic period 2017 ", had as purpose to determine the incidence of Organic law application for Economy Reactivation, Strengthening of the Dollarization and Financial Management Modernization, which entered into validity on January 1, 2018, introducing new benefits and tax incentives based on the promotion of new jobs and the fight against tax evasion. The methodology used has a quantitative approach, descriptive, explanatory, bibliographic and documentary. As research techniques, the survey and interviews were used through the application of interview guides and a questionnaire, respectively. The population was composed of 11 employees of the floriculture and its size it did not obtain a sample. This investigation determined the activities, objects and involved people in the process, this new law by collecting existing data between the study variables and based on a theory based on methods. In general terms it was possible to demonstrate that the floriculture exporter does not apply legal regulation, so it is recommended to socialize this law that will positively affect the payment reduction of incoming taxes and repayment at the end of foreign currency.